The genital atrium armature of some Brazilian sand fly females (Diptera: Phlebotominae) - Farias, Emanuelle de Sousa; Alencar, Ronildo Baiatone; Justiniano, Sílvia Brandão; Freitas, Jorge Alves de; Coelho, Luiz Souza de; Ríos-Velásquez, Cláudia María; Pessoa, Felipe Arley Costa (Acta Amazonica, 2015)
Phlebotomine sand flies are insects of medical importance. Species in the Neotropical region are highly diverse. Some of these species are considered cryptic species because of their morphological similarity between adult females of different species make identification especially difficult. The aim of this study was to analyze and describe the armature in the genital atrium (AGA) of some adult female sand flies, in order to discover new taxonomic characters that make it possible to distinguish between species that would otherwise be treated as cryptic by analysis of the AGA. The AGA of 16 Phlebotomine sand fly species are described. Distinct differences were found in relation to the shape and size of the armature, the presence or absence of spines on the armature, and the shape, size, and grouping patterns of the spines. These characters made it possible to distinguish between the species studied.
Armadura do átrio genital de algumas fêmeas de flebotomíneos brasileiros (Diptera: Phlebotominae)
Keywords: Cryptic species; Taxonomy; Morphology; Espécies Crípticas; Taxonomia; Morfologia